Mediation Test of Affective Commitment on the Influence of Perceptions of Organizational Support and Transformational Leadership on Employee Performance - Anggita, Sangga Wishnu; Fitriati, Azmi; Astuti, Herni Justiana; Widhiandono, Hengky (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Employees play an important role in achieving optimal performance and sustainable competitive advantage as expected. Therefore, special attention needs to be paid to employee development and support. This research aims to analyze and explore the influence of perceptions of organizational support and transformational leadership on affective commitment and employee performance. The population of this study was all employees who worked in the BLUD of Majenang Hospital, Cilacap Regency, Central Java, Indonesia. Sampling in this research used an accidental sampling technique. The data obtained in this research was processed statistically using Structural Equation Modeling (SEM). Based on the results of the data analysis of 278 respondents, this research concludes that POS has no effect on employee performance, but has a positive effect on affective commitment. POS also does not affect employee performance with affective commitment as an intervening factor. Other results show that transformational leadership has a positive effect on affective commitment and employee performance. Transformational leadership also has a positive effect on employee performance with affective commitment as an intervention. The results of this research can theoretically and practically be used by all related parties to improve employee performance and maintain sustainable competitive advantage.